2002
DOI: 10.1002/cncr.10273
|View full text |Cite
|
Sign up to set email alerts
|

Breast carcinoma in women age 25 years or less

Abstract: BACKGROUNDAlthough several studies have examined breast carcinoma in young women aged ≤ 35 years at diagnosis, there are only occasional cases reported in very young women aged ≤ 25 years, and, to the authors' knowledge, no series are available. The presentation, tumor biology, behavior, and outcome of breast carcinoma in very young women are not known, and the rarity of breast malignancy within this age group could lead to diagnostic delays.METHODSThe tumor characteristics and survival of 15 women aged ≤ 25 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 16 publications
1
41
0
7
Order By: Relevance
“…Younger age has been shown to be a poor prognosticator in breast cancer. Recently, Maggard and others have demonstrated that younger (o35) women with breast cancer have a poorer prognosis owing to higher stage and grade of disease at presentation (Yildirim et al, 2000;Biffl et al, 2001;Xiong et al, 2001;Dubsky et al, 2002;Kothari et al, 2002;Love et al, 2002;Maggard et al, 2003). However, studies on the prognostic implications of age and ovarian cancer are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age has been shown to be a poor prognosticator in breast cancer. Recently, Maggard and others have demonstrated that younger (o35) women with breast cancer have a poorer prognosis owing to higher stage and grade of disease at presentation (Yildirim et al, 2000;Biffl et al, 2001;Xiong et al, 2001;Dubsky et al, 2002;Kothari et al, 2002;Love et al, 2002;Maggard et al, 2003). However, studies on the prognostic implications of age and ovarian cancer are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer occurrence is increasing worldwide, with the largest number of cases being reported during perimenopause [1,2]. Conversely, both literature and current practice shows that patients with breast cancer are rare under the age of 30 [1,2,6].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, both literature and current practice shows that patients with breast cancer are rare under the age of 30 [1,2,6]. Using as a pretext the "chance" to encounter such a case in the hospital and relating it to the information provided by literature, we attempted to point out some of the peculiarities and paradoxes of the disease course in young women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations